CD59 mediates cartilage patterning during spontaneous tail regeneration - Bai, Xue (Sci Rep, 2015)
The regeneration-competent adult animals have ability to regenerate their lost complex appendages with a near-perfect replica, owing to the positional identity acquired by the progenitor cells in the blastema, i.e. the blastemal cells. CD59, a CD59/Ly6 family member, has been identified as a regulator of positional identity in the tail blastemal cells of Gekko japonicus. To determine whether this function of CD59 is unique to the regenerative amniote(s) and how CD59 mediates PD axis patterning during tail regeneration, we examined its protective role on the complement-mediated cell lysis and intervened CD59 expression in the tail blastemal cells using an in vivo model of adenovirus transfection. Our data revealed that gecko CD59 was able to inhibit complement-mediated cell lysis. Meanwhile, CD59 functioned on positional identity through expression in cartilage precursor cells. Intervening positional identity by overexpression or siRNA knockdown of CD59 resulted in abnormal cartilaginous cone patterning due to the decreased differentiation of blastemal cells to cartilage precursor cells. The cartilage formation-related genes were found to be under the regulation of CD59. These results indicate that CD59, an evolutionarily transitional molecule linking immune and regenerative regulation, affects tail regeneration by mediating cartilage patterning.